1997
DOI: 10.1111/j.2042-7174.1997.tb00902.x
|View full text |Cite
|
Sign up to set email alerts
|

Supplying injecting equipment to drug misusers: a survey of community pharmacists' attitudes, beliefs and practices

Abstract: A postal survey of 888 community pharmacists in one metropolitan administrative region of southern England investigated the pharmacists' involvement in the supply of injecting equipment to injecting drug misusers (IDMs). The survey response rate was 59 per cent. Of respondents, 58 per cent sold injecting equipment and almost 10 per cent supplied it via “exchange” schemes. The respondents' attitudes and beliefs towards provision of injecting equipment were measured on a five point scale. Providers of injecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…Pharmacists were more likely to offer harm reduction services if their location and situation demanded them and pharmacists had a diverse set of attitudes toward the IDU population, ranging from sympathy and remorse to apathy and disdain. 32,33 Studies in the United States have revealed similar data with respect to the recognized need for harm reduction services in community pharmacies. A survey of Rhode Island practitioners found that pharmacists felt it was their role to provide equipment and advice to IDUs to prevent the spread of infections and that providing these services in the community pharmacy setting would not disrupt regular pharmacy services.…”
Section: 31mentioning
confidence: 88%
“…Pharmacists were more likely to offer harm reduction services if their location and situation demanded them and pharmacists had a diverse set of attitudes toward the IDU population, ranging from sympathy and remorse to apathy and disdain. 32,33 Studies in the United States have revealed similar data with respect to the recognized need for harm reduction services in community pharmacies. A survey of Rhode Island practitioners found that pharmacists felt it was their role to provide equipment and advice to IDUs to prevent the spread of infections and that providing these services in the community pharmacy setting would not disrupt regular pharmacy services.…”
Section: 31mentioning
confidence: 88%
“…Attitudes towards service provision and the client are an important factor in the quality of services provided, and training may, to a certain extent, help deal with some of the less appropriate beliefs and attitudes (McCarty, Riechmann, Green, Gallon, & Knudsen, 2004). Rees (Rees, Harding, & Taylor, 1997) surveyed pharmacist involvement in, and attitudes and beliefs about, the supply of injecting equipment to injecting drug users (IDUs). Providers of injecting equipment to IDUs were shown to be significantly more likely than non-providers to have a positive attitude towards supply, to perceive greater demand for injecting equipment, and to believe that 'important others', such as the pharmacy customers and other health professionals, would like them to make equipment available.…”
Section: Introductionmentioning
confidence: 99%
“…Of note is that pharmacists in their capacity as health providers are more likely to provide harm reduction services if their communities demand them. 1,[16][17][18][19][33][34] Pharmacist experiences illustrated the positive nature of providing needle exchange services In contrast, findings elsewhere have illustrated more negative views, where some pharmacists have disclosed negative attitudes towards PWID and although attitudes towards the provision of services in pharmacies for PWID have generally improved in recent years they are still mixed. [35][36][37] Recent systematic reviews have underscored the general positive attitude to providing harm reduction advice in pharmacies, with common barriers centring on lack of time and specific training, fear of attracting difficult service users, insufficient remuneration, and difficulties in communicating with adjunct health providers.…”
Section: Discussionmentioning
confidence: 99%